Information Disclosure via Platform Endorsement in Online Health Care - Zhan, Jiajia; Zhang, Xu; Fu, Hongqiao (Journal of Marketing Research, 2026)
Platform endorsement is becoming increasingly popular and plays a critical role in online health care platforms by aiding patient choices and shaping doctors’ decisions. Using a unique dataset from a major Chinese online doctor consultation platform, this study applies a generalized synthetic control method to examine the impact of endorsement on patient demand, doctor service pricing, quantity, and quality. The findings show that endorsement significantly increases the price and quantity of paid services, while reducing free services among endorsed doctors. Despite handling higher service volumes, endorsed doctors maintain or improve quality. The endorsement program generates greater revenue for endorsed doctors and the platform, but it raises concerns about equity in health care access due to reduced free service provision for underprivileged patients. The analysis further reveals that the impact of endorsement varies between initial endorsement and reendorsement as well as between high-prosocial and low-prosocial doctors. These findings underscore the nuanced role of information disclosure in shaping doctor behavior and patient access, offering important implications for platform design.